THEORY AND PRACTICE IN TEACHING ENGLISH ECONOMICSVOCABULARY - Tascovici, Daliana Ecaterina; Platon, Carolina (Journal of Economic Development, Environment and People, 2017)
The present paper proposes to speak about teaching English economics vocabulary. So, at first, we make references to the key points and the issues which are raised by teaching and learning specific vocabulary: learners usually select the words they want to achieve; once learned, words move between active to passive status; one of teachers’ activities is to help students remember the acquired vocabulary; teachers should provide the correct exposure to words and opportunities for learners to practice them. Secondly, we will study examples of economics vocabulary teaching and show how discovery techniques can aid vocabulary acquisition. In the end we draw the conclusions, showing the importance and the active role of the discovery techniques in teaching English vocabulary.